Low dose monosodium glutamate induced oxidative damage and histopathological changes on the renal of male rats - Siti Fathiah Masre,; Nur Naimah Nani,; Nurul Athirah Razali,; Nur Afizah Yusoff,; Izatus Shima Taib, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Monosodium glutamate (MSG) is a flavour enhancer commonly used in processed food to increase palatability. Several studies have reported that chronic exposure of MSG causes renal fibrosis via oxidative stress mechanism. However, till date, the effects of low dose of MSG on the oxidative stress status and its histopathological observation of renal are still unclear. A total of 18 male Sprague Dawley rats (170 – 200 g) were divided randomly into three groups consisted of the control (received distilled water = 1 ml/kg), MSG 60 (received 60 mg/kg MSG) and MSG 120 (received 120 mg/kg MSG) groups. All of the substances were given via force-feed oral for 28 consecutive days. At the end of the study, all rats were sacrificed and the renal were isolated for biochemical and histological evaluation. The superoxide dismutase (SOD) activity and protein carbonyl (PC) level showed significantly increased (p < 0.05) in MSG 60 and MSG 120 group compared to the control group. However, no significant difference was found in glutathione (GSH) and malondialdehyde (MDA) level in all treated groups. The histology observation showed glomerulus shrinkage in MSG 60 and MSG 120 groups. In conclusion, these findings confirmed low dose of MSG-induced oxidative stress and histopathological changes on the renal of male Sprague-dawley rats. Accordingly, care must be taken on the intake of MSG in our daily basis.